Pemanfaatan Sampah Plastik Menjadi Material Konstruksi Modular Ecobrick Untuk Membentuk Karakter Penjaga Sungai Pada Anak-Anak - Wulandari, Tika Ermita; Yulina, Eva; Suranto, Suranto; Lubis, Faiz Azmi (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The ecosystem crisis along the Deli Riverbanks, driven by the accumulation of plastic waste, demands technical solutions that are both educational and sustainable. This community service program aims to transform domestic waste into modular construction materials using the ecobrick method while simultaneously fostering environmental character among children in Jalan Badur. The methods employed included audio-visual literacy sessions, collective waste collection actions, and technical workshops on modular material production. The results demonstrate that participants were capable of producing ecobricks that meet the density criteria for simple building materials. Beyond the technical success, the program yielded positive impacts on ecological behavioral changes and improved health aspects through nutritional assistance. The strategic value of this initiative lies in the conversion of waste into functional products (a civil engineering approach) integrated with behavioral psychology interventions and public health awareness.